THE COMPARATIVE EFFECTIVENESS OF PASSENGER CARS WITH DIFFERENT NUMBER OF SEATS - Gnennyi, O. M. (Science and Transport Progress, 2008)
The article defines the criterion of economic efficiency which allows comparing the coaches with different quantity of passenger places from the viewpoint of railways, in market conditions, from marketing principles of management. The major factors influencing on efficiency of coaches are revealed. The methods to define indicators of the efficiency taking into account these factors are developed.